Model internalisasi nilai antikorupsi melalui koperasi kejujuran pada siswa sekolah dasar - Nur Rahmawati, Zahra (Maliki Interdisciplinary Journal, 2026)
Corruption is a serious problem that leads to economic losses, moral decay, a decline in public trust in public institutions, and hinders national development. Efforts to eradicate corruption cannot be achieved solely through legal measures but must also include anti-corruption education starting at an early age to foster integrity. This article aims to formulate a model for the internalization of anti-corruption values through an honesty cooperative among elementary school students as a strategy to strengthen character education. This model integrates anti-corruption education, the process of value internalization, and practical application through the “honesty cooperative” as a contextual learning medium. The process of value internalization is carried out through habit formation, teacher modeling, reinforcement of positive behavior, and direct experience, so that anti-corruption values such as honesty, responsibility, discipline, justice, and compassion are deeply ingrained in the students. The expected outcome is the development of student’s character honest, disciplined, responsible, and capable of rejecting corrupt behavior. Thus, this model functions not only as a learning strategy but also as a preventive measure in building an anti-corruption culture within schools and the broader community.